Correlates of tobacco product cessation among youth and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016). (22nd April 2020) - Kasza, Karin A; Edwards, Kathryn C; Tang, Zhiqun; Stanton, Cassandra A; Sharma, Eva; Halenar, Michael J; Taylor, Kristie A; Donaldson, Elisabeth A; Hull, Lynn C; Bansal-Travers, Maansi; Limpert, Jean; Zandberg, Izabella; et al.
Abstract : Objective: To report on demographic and tobacco use correlates of cessation behaviours across tobacco products (cigarettes, electronic nicotine delivery systems (ENDS), cigars, hookah and smokeless tobacco) among the US population. Design: Data were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US youth (ages 12–17) and adults (ages 18+) . Past 30-day (P30D) tobacco users at Wave 1 (W1) or Wave 2 (W2) were included (n=1374 youth; n=14 389 adults). Generalised estimating equations were used to evaluate the association between demographic and tobacco use characteristics at baseline, with cessation behaviours at follow-up (discontinuing use, attempting to quit, quitting), over two 1-year periods (W1–W2, W2–Wave 3). Results: Among adult users of each type of tobacco product, frequency of use was negatively associated with discontinuing use. Among adult cigarette smokers, non-Hispanic white smokers, those with lower educational attainment and those with lower household income were less likely to discontinue cigarette use; ENDS use was positively associated with making quit attempts but was not associated with cigarette quitting among attempters; smokeless tobacco use was positively associated with quitting among attempters; tobacco dependence was negatively associated with quitting among attempters. Among youth cigarette smokers, tobacco dependence was negatively associated with making quit attempts. Discussion: Demographic correlates of tobacco cessation behaviours underscore tobacco use disparities in the USA. Use of ENDS and use of smokeless tobacco products are positively associated with some adult cigarette cessation behaviours.